Conductive polymer-containing liquid and conductive laminate
The conductive polymer-containing liquid, comprising a π-conjugated conductive polymer and polyanion modified by a quaternary ammonium compound, addresses the issue of conductivity loss in conductive layers by improving dispersion stability and maintaining low surface resistivity under atmospheric exposure.
Patent Information
- Application Number
- JP2021138611
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-08-27
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2041-08-27
AI Technical Summary
Conductive layers formed from π-conjugated conductive polymers deteriorate in conductivity over time when exposed to the atmosphere.
A conductive polymer-containing liquid is formulated with a π-conjugated conductive polymer, polyanion modified by a quaternary ammonium compound, acrylic monomers, urethane acrylate, and an organic solvent, which improves dispersion stability and resistance to atmospheric exposure.
The conductive layer maintains low surface resistivity, increasing by 10 times or less after 10 days of atmospheric exposure, demonstrating enhanced resistance to environmental degradation.
Smart Images

Figure 0007621222000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive polymer-containing liquid that contains a π-conjugated conductive polymer, and a conductive laminate. [Background technology]
[0002] A π-conjugated conductive polymer, whose main chain is composed of a π-conjugated system, forms a conductive complex by doping with a polyanion having an anion group, and becomes dispersible in water. A conductive film having a conductive layer can be manufactured by applying a conductive polymer-containing liquid (sometimes called a conductive polymer dispersion) containing the conductive complex to a film substrate or the like. In addition, an epoxy compound may be reacted with the conductive complex in order to increase the wettability of the conductive polymer-containing liquid to the film substrate or to increase the conductivity of the conductive layer to be formed. Furthermore, as a technique for suppressing the decrease in the conductivity of a conductive layer containing a conductive complex over time in the atmosphere, for example, Patent Document 1 discloses a method of including an aromatic compound represented by a specific chemical formula in the conductive layer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2020-143202 A Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention provides a conductive laminate having a conductive layer with improved resistance to exposure to the atmosphere, and a conductive polymer-containing liquid capable of forming the conductive layer. [Means for solving the problem]
[0005] [1] A conductive polymer-containing liquid containing a conductive complex including a π-conjugated conductive polymer and a polyanion, an organic solvent, one or more acrylic monomers, and a urethane acrylate other than the acrylic monomers, wherein the polyanion is modified by a reaction between a portion of an anionic group of the polyanion and a quaternary ammonium compound. [2] The conductive polymer-containing liquid according to [1], further containing a photopolymerization initiator. [3] The conductive polymer-containing liquid according to [1] or [2], further comprising a silica compound. [4] The conductive polymer-containing liquid according to any one of [1] to [3], wherein the organic solvent contains at least one selected from the group consisting of isopropyl alcohol, methyl ethyl ketone, and propylene glycol monomethyl ether. [5] The conductive polymer-containing liquid according to any one of [1] to [4], wherein the acrylic monomer includes at least one selected from the group consisting of pentaerythritol triacrylate, pentaerythritol tetraacrylate, 2-hydroxyethylacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, and N-acroylmorpholine. [6] The conductive polymer-containing liquid according to any one of [1] to [5], wherein the π-conjugated conductive polymer contains poly(3,4-ethylenedioxythiophene) or the polyanion contains polystyrenesulfonic acid. [7] The conductive polymer-containing liquid according to any one of [1] to [6], wherein the quaternary ammonium compound has at least one hydrocarbon group having 4 to 32 carbon atoms. [8] The conductive polymer-containing liquid according to any one of [1] to [7], wherein the quaternary ammonium compound contains tetraoctylammonium. [9] A conductive laminate comprising a substrate and a conductive layer formed on at least a portion of the substrate, the conductive layer being made of a cured product of the conductive polymer-containing liquid according to any one of [1] to [8].
[10] The conductive laminate according to [9], wherein an increase in the surface resistivity of the conductive layer of the conductive laminate is suppressed to 10 times or less before and after an atmospheric exposure experiment in which the conductive laminate is placed in a 25°C environment and exposed to the atmosphere for 10 days. Effect of the Invention
[0006] According to the conductive polymer-containing liquid of the present invention, a conductive layer having excellent resistance to exposure to the atmosphere can be formed. The conductive laminate of the present invention includes a conductive layer having excellent resistance to exposure to the atmosphere.
[0007] This invention is believed to contribute to SDGs Goal 12, "Responsible Consumption and Production." DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] In this specification and claims, the lower limit and upper limit of a numerical range indicated with "to" are included in the numerical range.
[0009] ≪Conductive polymer-containing liquid≫ A first aspect of the present invention is a conductive polymer-containing liquid that contains a conductive complex containing a π-conjugated conductive polymer and a polyanion, an organic solvent, one or more types of acrylic monomers, and a urethane acrylate. The polyanion is modified by reacting a portion of the anionic groups of the polyanion with a quaternary ammonium compound, and the dispersibility in isopropyl alcohol is particularly improved. In the conductive polymer-containing liquid of this embodiment, the conductive complex may be in a dispersed state or a dissolved state. In this specification, unless otherwise specified, the dispersed state and the dissolved state are not distinguished, and may simply be referred to as the dispersed state.
[0010] [Conductive composite] The conductive complex contained in the conductive polymer-containing liquid of this embodiment contains a π-conjugated conductive polymer and a polyanion. The polyanion in the conductive complex is doped into the π-conjugated conductive polymer to form a conductive complex having electrical conductivity. In the polyanion, only a part of the anionic groups is doped into the π-conjugated conductive polymer, and there are excess anionic groups that are not involved in the doping. Since the excess anionic groups are hydrophilic groups, the conductive composite in which the excess anionic groups are not modified has water dispersibility.
[0011] (π-conjugated conductive polymer) The π-conjugated conductive polymer may be an organic polymer whose main chain is composed of a π-conjugated system, and examples thereof include polypyrrole-based conductive polymers, polythiophene-based conductive polymers, polyacetylene-based conductive polymers, polyphenylene-based conductive polymers, polyphenylenevinylene-based conductive polymers, polyaniline-based conductive polymers, polyacene-based conductive polymers, polythiophenevinylene-based conductive polymers, and copolymers thereof. From the viewpoint of stability in air, polypyrrole-based conductive polymers, polythiophenes, and polyaniline-based conductive polymers are preferred, and from the viewpoint of transparency, polythiophene-based conductive polymers are more preferred.
[0012] Polythiophene-based conductive polymers include polythiophene, poly(3-methylthiophene), poly(3-ethylthiophene), poly(3-propylthiophene), poly(3-butylthiophene), poly(3-hexylthiophene), poly(3-heptylthiophene), poly(3-octylthiophene), poly(3-decylthiophene), poly(3-dodecylthiophene), poly(3-octadecylthiophene), poly(3-bromothiophene), poly(3-chlorothiophene), and poly(3-iodothiophene). thiophene), poly(3-cyanothiophene), poly(3-phenylthiophene), poly(3,4-dimethylthiophene), poly(3,4-dibutylthiophene), poly(3-hydroxythiophene), poly(3-methoxythiophene), poly(3-ethoxythiophene), poly(3-butoxythiophene), poly(3-hexyloxythiophene), poly(3-heptyloxythiophene), poly(3-octyloxythiophene), poly(3-decyloxythiophene), poly(3-dodecyloxythiophene), oxythiophene), poly(3-octadecyloxythiophene), poly(3,4-dihydroxythiophene), poly(3,4-dimethoxythiophene), poly(3,4-diethoxythiophene), poly(3,4-dipropoxythiophene), poly(3,4-dibutoxythiophene), poly(3,4-dihexyloxythiophene), poly(3,4-diheptyloxythiophene), poly(3,4-dioctyloxythiophene), poly(3,4-didecyloxythiophene), poly(3,4-di dodecyloxythiophene), poly(3,4-ethylenedioxythiophene), poly(3,4-propylenedioxythiophene), poly(3,4-butylenedioxythiophene), poly(3-methyl-4-methoxythiophene), poly(3-methyl-4-ethoxythiophene), poly(3-carboxythiophene), poly(3-methyl-4-carboxythiophene), poly(3-methyl-4-carboxyethylthiophene), and poly(3-methyl-4-carboxybutylthiophene). Examples of polypyrrole-based conductive polymers include polypyrrole, poly(N-methylpyrrole), poly(3-methylpyrrole), poly(3-ethylpyrrole), poly(3-n-propylpyrrole), poly(3-butylpyrrole), poly(3-octylpyrrole), poly(3-decylpyrrole), poly(3-dodecylpyrrole), poly(3,4-dimethylpyrrole), poly(3,4-dibutylpyrrole), poly(3-carboxypyrrole), poly(3-methyl-4-carboxypyrrole), poly(3-methyl-4-carboxyethylpyrrole), poly(3-methyl-4-carboxybutylpyrrole), poly(3-hydroxypyrrole), poly(3-methoxypyrrole), poly(3-ethoxypyrrole), poly(3-butoxypyrrole), poly(3-hexyloxypyrrole), and poly(3-methyl-4-hexyloxypyrrole). Examples of polyaniline-based conductive polymers include polyaniline, poly(2-methylaniline), poly(3-isobutylaniline), poly(2-anilinesulfonic acid), and poly(3-anilinesulfonic acid). Among these π-conjugated conductive polymers, poly(3,4-ethylenedioxythiophene) is particularly preferable because of its excellent conductivity, transparency, and heat resistance. The conductive composite may contain one type of π-conjugated conductive polymer, or two or more types of polymers.
[0013] (Polyanion) A polyanion is a polymer having two or more monomer units each having an anionic group in the molecule. The anionic group of the polyanion functions as a dopant for a π-conjugated conductive polymer, improving the conductivity of the π-conjugated conductive polymer. The anion group of the polyanion is preferably a sulfo group or a carboxy group. Specific examples of such polyanions include polymers having a sulfo group, such as polystyrene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyacrylic acid esters having a sulfo group, polymethacrylic acid esters having a sulfo group (for example, poly(4-sulfobutyl methacrylate, polysulfoethyl methacrylate, polymethacryloyloxybenzenesulfonic acid), poly(2-acrylamido-2-methylpropanesulfonic acid), and polyisoprene sulfonic acid; and polymers having a carboxy group, such as polyvinyl carboxylic acid, polystyrene carboxylic acid, polyallyl carboxylic acid, polyacrylic acid, polymethacrylic acid, poly(2-acrylamido-2-methylpropanecarboxylic acid), and polyisoprene carboxylic acid. The polyanion may be a homopolymer in which a single monomer is polymerized, or a copolymer in which two or more monomers are polymerized. Among these polyanions, polymers having a sulfo group are preferred, and polystyrene sulfonic acid is more preferred, since they can provide higher electrical conductivity. The polyanions may be used alone or in combination of two or more kinds. The mass average molecular weight of the polyanion is preferably from 20,000 to 1,000,000, and more preferably from 100,000 to 500,000. The mass average molecular weight of the polyanion is the average molecular weight based on mass measured using gel filtration chromatography and calculated in terms of pullulan.
[0014] When the number of all anionic groups in the polyanion is taken as 100 mol %, the excess anionic groups are preferably from 30 mol % to 90 mol %, more preferably from 45 mol % to 75 mol %.
[0015] The polyanion of the present invention is modified by reacting the excess anion groups (hereinafter also referred to as "part of the anion groups") of the polyanion that are not involved in the dope with a quaternary ammonium compound. That is, the polyanion of the present invention has a substituent (C) formed by reacting the quaternary ammonium compound with the part of the anion groups.
[0016] (Substituent C) The substituent (C) is presumed to be a group represented by the following formula (C).
[0017] -N + R 11 R 12 R 13 R 14 (C) [In formula (C), R 11 ~R 14 each independently represents a hydrocarbon group which may have a substituent.
[0018] In the substituent (C), the bond at the left end represents the bond between the negative charge of the anion group and the positive charge of the quaternary ammonium cation. Examples of an anion group that can be negatively charged include "-SO3 - " is an anionic group in which an active proton is bonded to an oxygen atom.
[0019] R in chemical formula (C) 11 ~R 14 R in chemical formula (C) is a hydrocarbon group which may have a substituent. 11 ~R 14 is a substituent derived from a quaternary ammonium compound. Examples of the hydrocarbon group in the chemical formula (C) include an aliphatic hydrocarbon group having 1 to 32 carbon atoms which may have a substituent, and an aromatic hydrocarbon group having 6 to 20 carbon atoms which may have a substituent. Examples of the aliphatic hydrocarbon group include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, and an octyl group. Examples of the substituent on the aliphatic hydrocarbon group include a phenyl group and a hydroxyl group. Examples of the aromatic hydrocarbon group include a phenyl group and a naphthyl group. Examples of the substituent on the aromatic hydrocarbon group include an alkyl group having 1 to 5 carbon atoms and a hydroxyl group.
[0020] In order to improve dispersibility in organic solvents and conductivity, the quaternary ammonium compound preferably has a substituent on the nitrogen atom having 3 or more carbon atoms, more preferably has a substituent on the nitrogen atom having 5 or more carbon atoms, and even more preferably has a substituent on the nitrogen atom having 7 or more carbon atoms. The upper limit of the carbon number of each substituent on the nitrogen atom is not particularly limited, and taking into consideration solubility in solvents and reactivity, it is, for example, preferably 40 or less, more preferably 30 or less, and even more preferably 20 or less. In addition, the R 11 ~R 14 The total number of carbon atoms is preferably 8 to 44, more preferably 12 to 40, and further preferably 16 to 36. The number of carbon atoms in each of the substituents on the nitrogen atom may be the same or different.
[0021] In addition, the quaternary ammonium compound preferably has at least one hydrocarbon group having 4 to 32 carbon atoms, since this improves dispersibility in organic solvents and improves electrical conductivity.
[0022] The quaternary ammonium compound is preferably a tetraalkylammonium halide, because it has high reactivity with polyanions, and the reaction product is difficult to dissolve in the aqueous dispersion medium and easily precipitates. As the halogen ion of the counter anion, a bromide ion or a chloride ion is preferable, and a bromide ion is more preferable.
[0023] Specific examples of quaternary ammonium compounds include quaternary ammonium salts such as tetramethylammonium salt, tetraethylammonium salt, tetrapropylammonium salt, tetrabutylammonium salt, tetra-n-octylammonium salt, tetraphenylammonium salt, tetrabenzylammonium salt, and tetranaphthylammonium salt. Examples of the counter anion of the ammonium cation include halogen ions such as bromide ion and chloride ion, and hydroxy ion.
[0024] The content of the polyanion in the conductive complex is preferably in the range of 1 part by mass to 1000 parts by mass, more preferably 10 parts by mass to 700 parts by mass, and even more preferably 100 parts by mass to 500 parts by mass, per 100 parts by mass of the π-conjugated conductive polymer. If the content of the polyanion is equal to or greater than the lower limit, the doping effect on the π-conjugated conductive polymer tends to be stronger, and the conductivity becomes higher. On the other hand, if the content of the polyanion is equal to or less than the upper limit, the amount of anion groups not involved in doping is appropriately suppressed, and the anion groups can be easily converted to hydrophobicity when reacting with a quaternary ammonium compound.
[0025] The content of the conductive complex relative to the total mass of the conductive polymer-containing liquid is, for example, preferably 0.01% by mass to 5% by mass, more preferably 0.05% by mass to 1% by mass, and even more preferably 0.1% by mass to 0.6% by mass. When the content is in the above preferred range, the dispersion stability of the conductive complex is improved.
[0026] [Acrylic Monomer] The acrylic monomer of this embodiment is a known polymerizable compound having a (meth)acrylic group (also known as a (meth)acryloyl group). Here, the term "(meth)acrylic" means "acrylic or methacrylic", and the term "(meth)acryloyl" means "acryloyl or methacryloyl". The (meth)acrylic group includes a (meth)acryloxy group. The acrylic monomer of this embodiment is a polymerizable acrylic compound other than urethane acrylate.
[0027] From the viewpoint of improving dispersibility in the conductive polymer-containing liquid and improving reactivity during curing of the conductive polymer-containing liquid, the molecular weight of the acrylic monomer is preferably 1000 or less, more preferably 500 or less. The lower limit of the molecular weight of the acrylic monomer is not particularly limited, and is usually 100 or more.
[0028] The number of (meth)acrylic groups in the acrylic monomer molecule may be 1 or 2 or more. From the viewpoint of increasing the hardness of the conductive polymer-containing liquid when cured, the number is preferably 2 or more, and more preferably 3 or more. The upper limit of the number is not particularly limited, and from the viewpoint of easy availability of commercial products, it is preferably 6 or less, and more preferably 5 or less.
[0029] Examples of acrylic monomers include (meth)acrylates (also known as (meth)acrylic acid esters) and (meth)acrylamides. From the viewpoint of enhancing the resistance to atmospheric exposure of the conductive layer made of the conductive polymer-containing liquid of this embodiment, it is preferable that the conductive polymer-containing liquid contains both (meth)acrylate and (meth)acrylamide.
[0030] Examples of (meth)acrylates include (meth)acrylates having a linear, branched or cyclic monovalent hydrocarbon group (e.g., an alkyl group) having 1 to 12 carbon atoms at the end of the ester group. Here, one or more hydrogen atoms bonded to the monovalent hydrocarbon group may be substituted with another (meth)acrylic group. When the (meth)acrylate has two or more (meth)acrylic groups, one (meth)acrylic group is arbitrarily selected, and the number of carbon atoms of the monovalent hydrocarbon group ester-bonded to the selected (meth)acrylic group is counted, assuming that the remaining (meth)acrylic groups are hydrogen atoms. One or more hydrogen atoms (-H) constituting the monovalent hydrocarbon group of the (meth)acrylate may be substituted with a hydroxyl group. One or more methylene groups (-CH2-) constituting the monovalent hydrocarbon group of the (meth)acrylate may be substituted with an oxygen atom, so long as the oxygen atoms are not bonded to each other.
[0031] Examples of acrylates include 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 4-hydroxybutyl acrylate, isobornyl acrylate, tetrahydrofurfuryl acrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, polyethylene glycol diacrylate, 1,6-hexanediol diacrylate, bisphenol A·ethylene oxide modified diacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol hexaacrylate, dipentaerythritol pentaacrylate, dipentaerythritol monohydroxypentaacrylate, trimethylolpropane triacrylate, and glycerin propoxy triacrylate. Examples of methacrylates include n-butyl methacrylate, t-butyl methacrylate, benzyl methacrylate, 2-ethylhexyl methacrylate, cyclohexyl methacrylate, allyl methacrylate, 2-hydroxyethyl methacrylate, isobornyl methacrylate, lauryl methacrylate, phenoxyethyl methacrylate, glycidyl methacrylate, tetrahydrofurfuryl methacrylate, diethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, 1,3-butylene glycol dimethacrylate, 1,6-hexanediol dimethacrylate, and trimethylolpropane trimethacrylate. Examples of (meth)acrylamides include methacrylamide, 2-hydroxyethylacrylamide, N-methylacrylamide, Nt-butylacrylamide, N-isopropylacrylamide, N-phenylacrylamide, N-methylol acrylamide, dimethylaminopropylacrylamide, dimethylaminopropylmethacrylamide, diacetone acrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, N-vinylformamide, N-acryloylmorpholine, and acryloylpiperidine. Among these, from the viewpoint of further improving the hardness and resistance to atmospheric exposure of the conductive layer made of the conductive polymer-containing liquid, at least one selected from pentaerythritol triacrylate, pentaerythritol tetraacrylate, 2-hydroxyethylacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, and N-acroylmorpholine is particularly preferred.
[0032] The total content of one or more acrylic monomers relative to the total mass of the conductive polymer-containing liquid of this embodiment is preferably 5% by mass or more and 50% by mass or less, more preferably 10% by mass or more and 45% by mass or less, and even more preferably 15% by mass or more and 40% by mass or less. When the content is at least the lower limit of the above range, the hardness and resistance to exposure to the atmosphere of the conductive layer made of the conductive polymer-containing liquid can be further increased. When the content is equal to or less than the upper limit of the above range, a decrease in the conductivity of the conductive layer made of the conductive polymer-containing liquid can be suppressed.
[0033] The total content of the acrylic monomers contained in the conductive polymer-containing liquid of this embodiment is preferably 100 parts by mass or more and 1,000 parts by mass or less, more preferably 125 parts by mass or more and 700 parts by mass or less, and even more preferably 150 parts by mass or more and 500 parts by mass or less, relative to 1 part by mass of the conductive composite. When the content is at least the lower limit of the above range, the hardness and resistance to exposure to the atmosphere of the conductive layer made of the conductive polymer-containing liquid can be further increased. When the content is equal to or less than the upper limit of the above range, a decrease in the conductivity of the conductive layer made of the conductive polymer-containing liquid can be suppressed.
[0034] [Urethane acrylate] The urethane acrylate of this embodiment is a compound having at least one (meth)acryloyl group and at least one urethane group in the molecule. Urethane acrylates having two or more (meth)acryloyl groups are collectively called polyfunctional urethane acrylates. From the viewpoint of further increasing the hardness and air exposure resistance of the conductive layer made of the conductive polymer-containing liquid, the number of (meth)acryloyl groups (functional groups) contained in the urethane acrylate molecule is preferably 2 or more, more preferably 6 or more, even more preferably 8 or more, and particularly preferably 10 or more. As a guideline for the upper limit of this number, 20 or less can be mentioned.
[0035] Examples of urethane acrylates include those obtained by reacting one or more types of (meth)acrylates having a hydroxyl group with one or more types of polyisocyanates, those obtained by reacting one or more types of (meth)acrylates having an isocyanate group with one or more types of polyols, and those obtained by reacting one or more types of (meth)acrylates having a hydroxyl group with one or more types of polyisocyanates and one or more types of polyols.
[0036] Examples of the (meth)acrylate having a hydroxyl group include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate.
[0037] Examples of the polyisocyanate include aromatic polyisocyanates such as tolylene diisocyanate, diphenylmethane diisocyanate, polyphenylmethane polyisocyanate, modified diphenylmethane diisocyanate, xylylene diisocyanate, tetramethylxylylene diisocyanate, phenylene diisocyanate, and naphthalene diisocyanate; aliphatic polyisocyanates such as pentamethylene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, lysine diisocyanate, and lysine triisocyanate; and alicyclic polyisocyanates such as hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, norbornene diisocyanate, and 1,3-bis(isocyanatomethyl)cyclohexane.
[0038] Examples of the polyol include polyether polyols such as polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polybutylene glycol, and polyhexamethylene glycol; and polyester polyols obtained as condensation polymers of polyhydric alcohols and polycarboxylic acids.
[0039] Examples of polyhydric alcohols include ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, trimethylene glycol, 1,4-tetramethylene diol, 1,3-tetramethylene diol, 2-methyl-1,3-trimethylene diol, 1,5-pentamethylene diol, neopentyl glycol, 1,6-hexamethylene diol, 3-methyl-1,5-pentamethylene diol, 2,4-diethyl-1,5-pentamethylene diol, glycerin, trimethylolpropane, trimethylolethane, cyclohexanediols (such as 1,4-cyclohexanediol), bisphenols (such as bisphenol A), and sugar alcohols (such as xylitol and sorbitol).
[0040] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids such as malonic acid, maleic acid, fumaric acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, and dodecanedioic acid; alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid; and aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, orthophthalic acid, 2,6-naphthalenedicarboxylic acid, paraphenylenedicarboxylic acid, and trimellitic acid.
[0041] The mass average molecular weight of the urethane acrylate is preferably from 1,000 to 100,000, more preferably from 2,000 to 50,000, and even more preferably from 3,000 to 10,000. Here, the mass average molecular weight of the urethane acrylate is the mass-average molecular weight measured by gel filtration chromatography and calculated in terms of polystyrene. When the content is at least the lower limit of the above range, the degree of hardening and resistance to exposure to the atmosphere of the conductive layer made of the conductive polymer-containing liquid can be further increased. When it is equal to or less than the upper limit of the above range, the dispersibility of the urethane acrylate in the conductive polymer-containing liquid is improved, and the reactivity of the conductive polymer-containing liquid during curing is increased, thereby enabling the degree of curing and resistance to exposure to the atmosphere of the formed conductive layer to be further improved.
[0042] The content of the urethane acrylate relative to the total mass of the conductive polymer-containing liquid of this embodiment is preferably from 0.1 to 20% by mass, more preferably from 0.5 to 10% by mass, and even more preferably from 1 to 5% by mass. When the content is at least the lower limit of the above range, the hardness and resistance to exposure to the atmosphere of the conductive layer made of the conductive polymer-containing liquid can be further increased. When the content is equal to or less than the upper limit of the above range, a decrease in the conductivity of the conductive layer made of the conductive polymer-containing liquid can be suppressed.
[0043] The content of the urethane acrylate contained in the conductive polymer-containing liquid of this embodiment is preferably 1 part by mass or more and 1,000 parts by mass or less, more preferably 10 parts by mass or more and 500 parts by mass or less, and even more preferably 10 parts by mass or more and 100 parts by mass or less, relative to 1 part by mass of the conductive composite. When the content is at least the lower limit of the above range, the hardness and resistance to exposure to the atmosphere of the conductive layer made of the conductive polymer-containing liquid can be further increased. When the content is equal to or less than the upper limit of the above range, a decrease in the conductivity of the conductive layer made of the conductive polymer-containing liquid can be suppressed.
[0044] [Silica compounds] The conductive polymer-containing liquid of this embodiment preferably contains one or more silica compounds. By containing a silica compound, the hardness and air exposure resistance of the conductive layer made of the conductive polymer-containing liquid can be further increased. Generally, the silica compound is a compound containing silicon oxide. The silica compound of this embodiment is preferably colloidal silica that has been granulated to such an extent that it can form a colloid in a dispersion medium. When silanol groups are present on the surface of the silica compound, the dispersibility in the organic solvent may decrease. From the viewpoint of improving the dispersibility in the organic solvent in the conductive polymer-containing liquid of this embodiment, it is preferable that at least a part of the silanol groups of the silica compound is hydrophobized by chemical modification. Silica compounds that have been subjected to such surface treatment are generally referred to as organosilica. Examples of organosilica include those obtained by silylation of colloidal silica with a disiloxane compound and / or a monoalkoxysilane compound.
[0045] The organosilica preferably has a reactive functional group capable of undergoing a radical polymerization reaction with the (meth)acryloyl group of the acrylic monomer and urethane acrylate. When the conductive polymer-containing liquid hardens, the silica compound is integrated with the acrylic monomer and the urethane acrylate, and the hardness and resistance to exposure to the atmosphere can be further improved. Examples of commercially available organosilica having such reactive functional groups include surface-modified grades of organosilica sol manufactured by Nissan Chemical Industries, Ltd., and the STA-SiA TAZ series manufactured by Taisei Fine Chemical Co., Ltd.
[0046] The content of the silica compound relative to the total mass of the conductive polymer-containing liquid of this embodiment is preferably 0.1 mass % to 10 mass %, more preferably 0.2 mass % to 6 mass %, and even more preferably 0.4 mass % to 4 mass %. When the content is at least the lower limit of the above range, the hardness and resistance to exposure to the atmosphere of the conductive layer made of the conductive polymer-containing liquid can be further increased. When the content is equal to or less than the upper limit of the above range, a decrease in the conductivity of the conductive layer made of the conductive polymer-containing liquid can be suppressed.
[0047] The content of the silica compound contained in the conductive polymer-containing liquid of this embodiment is preferably 1 part by mass or more and 1,000 parts by mass or less, more preferably 2 parts by mass or more and 500 parts by mass or less, and even more preferably 3 parts by mass or more and 100 parts by mass or less, relative to 1 part by mass of the conductive composite. When the content is at least the lower limit of the above range, the hardness and resistance to exposure to the atmosphere of the conductive layer made of the conductive polymer-containing liquid can be further increased. When the content is equal to or less than the upper limit of the above range, a decrease in the conductivity of the conductive layer made of the conductive polymer-containing liquid can be suppressed.
[0048] (Copolymerizable compound) The conductive polymer-containing liquid of this embodiment may contain another polymerizable compound copolymerizable with the acrylic monomer, as long as the effect of the present invention is not impaired. Examples of known polymerizable compounds that are known to be copolymerizable with the acrylic monomer include unsaturated carboxylic acids and derivatives thereof, such as maleic acid and itaconic acid, acid anhydrides and derivatives thereof, such as maleic anhydride and itaconic anhydride, vinyl esters, such as vinyl acetate and vinyl benzoate, vinyl chloride, vinylidene chloride and derivatives thereof, and aromatic vinyl compounds, such as styrene and α-methylstyrene. When the conductive polymer-containing liquid of this embodiment contains the above-mentioned polymerizable compound, the content thereof can be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the acrylic monomer.
[0049] [Polymerization initiator] The conductive polymer-containing liquid of this embodiment preferably contains a radical polymerization initiator. Examples of the radical polymerization initiator include a photopolymerization initiator and a thermal polymerization initiator. Among them, a photopolymerization initiator is preferred because the reaction can be easily controlled.
[0050] (Photopolymerization initiator) The photopolymerization initiators can be used alone or in combination of two or more. Examples of the photopolymerization initiator include known ones such as benzoin ether-based photopolymerization initiators, acetophenone-based photopolymerization initiators, α-ketol-based photopolymerization initiators, aromatic sulfonyl chloride-based photopolymerization initiators, photoactive oxime-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzyl-based photopolymerization initiators, benzophenone-based photopolymerization initiators, ketal-based photopolymerization initiators, thioxanthone-based photopolymerization initiators, and acylphosphine oxide-based photopolymerization initiators. Specific examples of benzoin ether-based photopolymerization initiators include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethane-1-one [trade name: Irgacure 651, manufactured by BASF], anisole methyl ether, etc. Examples of acetophenone-based photopolymerization initiators include 1-hydroxycyclohexyl phenyl ketone [trade name: Omnirad184, manufactured by IGM Resins], 4-phenoxydichloroacetophenone, 4-t-butyl-dichloroacetophenone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one [trade name: Irgacure 2959, manufactured by BASF], 2-hydroxy-2-methyl-1-phenyl-propan-1-one [trade name: Darocur 1173, manufactured by BASF], and methoxyacetophenone.
[0051] (Thermal polymerization initiator) The thermal polymerization initiators can be used alone or in combination of two or more. Examples of the thermal polymerization initiator include known azo initiators, persulfates, and peroxide initiators.
[0052] [Dispersion medium] The organic solvent contained in the conductive polymer-containing liquid of this embodiment is a dispersion medium that disperses the conductive complex that has been hydrophobized by reaction with the quaternary ammonium compound.
[0053] Examples of the organic solvent include hydrocarbon solvents, ketone solvents, alcohol solvents, ether solvents, and nitrogen atom-containing compound solvents. Examples of the hydrocarbon solvent include aliphatic hydrocarbon solvents and aromatic hydrocarbon solvents. Examples of the aliphatic hydrocarbon solvent include pentane, hexane, heptane, octane, decane, cyclohexane, methylcyclohexane, etc. Examples of the aromatic hydrocarbon solvent include benzene, toluene, xylene, ethylbenzene, propylbenzene, isopropylbenzene, etc. Examples of the ketone solvent include diethyl ketone, methyl propyl ketone, methyl butyl ketone, methyl isopropyl ketone, methyl isobutyl ketone, methyl amyl ketone, diisopropyl ketone, methyl ethyl ketone, acetone, and diacetone alcohol. Examples of the alcohol solvent include methanol, ethanol, isopropyl alcohol, 1-propanol, n-butanol, t-butanol, and allyl alcohol. Examples of the ether solvent include diethyl ether, dimethyl ether, propylene glycol dimethyl ether, and propylene glycol monomethyl ether. Examples of the nitrogen atom-containing compound solvent include N-methylpyrrolidone, dimethylacetamide, and dimethylformamide. Among the above, one or more selected from methyl ethyl ketone, isopropyl alcohol, and propylene glycol monomethyl ether are preferred.
[0054] From the viewpoint of enhancing the dispersion stability of the conductive composite in the conductive polymer-containing liquid of this embodiment, it is particularly preferable that the organic solvent contains isopropyl alcohol. The content of isopropyl alcohol relative to the total mass of the conductive polymer-containing liquid is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more. The upper limit of the content of isopropyl alcohol is, for example, 90% by mass or less, leaving room for the inclusion of the conductive complex and other components. When it is in the above preferred range, the dispersion stability of the conductive complex is improved, and the wettability to the substrate is also excellent.
[0055] The conductive polymer-containing liquid of this embodiment may contain a small amount of water. The water content of the conductive polymer-containing liquid is preferably 10% by mass or less, more preferably 5% by mass or less, further preferably 2% by mass or less, and particularly preferably 1% by mass or less, based on the total mass of the conductive polymer-containing liquid. When the water content is low, the dispersion stability of the conductive composite is improved, and the wettability to the substrate is also excellent.
[0056] (Other additives) The conductive polymer-containing liquid of this embodiment may contain other known additives. The additives are not particularly limited as long as the effects of the present invention can be obtained. For example, surfactants, inorganic conductive agents, antifoaming agents, coupling agents, antioxidants, ultraviolet absorbing agents, etc. can be used. The surfactant may be a nonionic, anionic or cationic surfactant, with the nonionic surfactant being preferred from the standpoint of storage stability. A polymer surfactant such as polyvinylpyrrolidone may also be added. Examples of the inorganic conductive agent include metal ions, conductive carbon, etc. Metal ions can be generated by dissolving a metal salt in water. The antifoaming agent includes silicone resin, polydimethylsiloxane, silicone oil, and the like. The coupling agent may be a silane coupling agent having a vinyl group or an amino group. Examples of the antioxidant include phenol-based antioxidants, amine-based antioxidants, phosphorus-based antioxidants, sulfur-based antioxidants, and sugars. Examples of the ultraviolet absorber include benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, salicylate-based ultraviolet absorbers, cyanoacrylate-based ultraviolet absorbers, oxanilide-based ultraviolet absorbers, hindered amine-based ultraviolet absorbers, and benzoate-based ultraviolet absorbers. When the conductive polymer-containing liquid of this embodiment contains the above-mentioned additive, the content ratio thereof is appropriately determined depending on the type of additive, but can be, for example, in the range of 0.001 parts by mass or more and 5 parts by mass or less per 100 parts by mass of the conductive composite.
[0057] <Method for producing conductive polymer-containing liquid> The conductive polymer-containing liquid of the first embodiment of the present invention can be obtained by mixing, in a conventional manner, a conductive complex that has been hydrophobized by reacting it with a quaternary ammonium compound, an acrylic monomer, a urethane acrylate, an organic solvent, and, as necessary, a silica compound, a polymerization initiator, and other additives.
[0058] The following method is preferred as a method for reacting the conductive complex with a quaternary ammonium compound: That is, a method is preferred in which a conductive polymer aqueous dispersion containing a conductive complex containing a π-conjugated conductive polymer and a polyanion is dropped into an organic solution (reaction liquid) containing a quaternary ammonium compound, a part of an anion group of the polyanion is reacted with the quaternary ammonium compound, and a reaction precipitation step is performed to precipitate a reaction product, a recovery step is performed to recover the reaction product, and a preparation step is performed to obtain an organic solvent solution of the conductive polymer by dispersing the recovered reaction product in an organic solvent. A washing step may be further included between the recovery step and the preparation step.
[0059] [Reaction precipitation process] This process is a process in which a conductive polymer aqueous dispersion is added to an organic solution (reaction liquid) containing a quaternary ammonium compound, thereby precipitating a reaction product between the conductive complex and the quaternary ammonium compound in the reaction liquid.
[0060] When the conductive polymer aqueous dispersion is added to the reaction solution, the quaternary ammonium compound reacts stably with some of the anion groups of the polyanion of the conductive complex, forming the aforementioned substituent (C) and making the conductive complex hydrophobic, improving the dispersion stability against isopropyl alcohol, making it difficult to stably disperse in the reaction solution, and causing precipitation to form a precipitate.
[0061] The organic solvent contained in the reaction liquid may be one type or two or more types. As the organic solvent, the organic solvents already exemplified can be used, and examples thereof include methanol, ethanol, 1-propanol, isopropyl alcohol, n-butanol, t-butanol, and allyl alcohol.
[0062] The content of the quaternary ammonium compound in the reaction liquid is preferably 10 parts by mass or more and 5,000 parts by mass or less, more preferably 100 parts by mass or more and 1,000 parts by mass or less, and even more preferably 150 parts by mass or more and 500 parts by mass or less, relative to 100 parts by mass of the total mass of the conductive complex added. When the content is at least the lower limit of the above range, the reaction efficiency between the conductive complex and the quaternary ammonium compound is increased, and the reaction product can be easily obtained. When the content is equal to or less than the upper limit of the above range, a decrease in the conductivity of the conductive composite due to contamination with unreacted quaternary ammonium compound can be prevented.
[0063] The conductive polymer aqueous dispersion is a dispersion in which a conductive complex containing a π-conjugated conductive polymer and a polyanion is contained in an aqueous dispersion medium. Here, the aqueous dispersion medium is water or a mixture of water and a water-soluble organic solvent. The water-soluble organic solvent is one that dissolves in an amount of 1 g or more per 100 g of water (20° C.). Examples of the water-soluble organic solvent include alcohol-based solvents, ketone-based solvents, and ester-based solvents. The aqueous dispersion medium may contain one type of water-soluble organic solvent, or two or more types of water-soluble organic solvents. The content of water relative to the total mass of the aqueous dispersion medium is preferably more than 50% by mass, more preferably 60% by mass or more, even more preferably 80% by mass or more, and may be 100% by mass. When the content of water is large, the dispersibility of the conductive composite is increased, and the reaction efficiency with the quaternary ammonium compound is increased. Furthermore, the reaction product is easily precipitated in the reaction liquid.
[0064] The conductive polymer aqueous dispersion can be obtained, for example, by chemically oxidizing a monomer that forms a π-conjugated conductive polymer in an aqueous solution of a polyanion. Alternatively, a commercially available conductive polymer aqueous dispersion can be used. A known catalyst may be used in the chemical oxidative polymerization. For example, a catalyst and an oxidizing agent may be used. Examples of the catalyst include transition metal compounds such as ferric chloride, ferric sulfate, ferric nitrate, and cupric chloride. Examples of the oxidizing agent include persulfates such as ammonium persulfate, sodium persulfate, and potassium persulfate.
[0065] The content of the π-conjugated conductive polymer and the polyanion relative to the total mass of the aqueous conductive polymer dispersion is preferably from 0.1% by mass to 5% by mass, more preferably from 0.5% by mass to 2% by mass, and even more preferably from 0.8% by mass to 1.5% by mass. When the content is within the above preferred range, the dispersibility of the conductive complex is improved, and the reaction efficiency with the quaternary ammonium compound is increased.
[0066] The volume ratio (V1 / V2) of the volume V2 of the conductive polymer aqueous dispersion to be added to the volume V1 of the reaction liquid is preferably from 0.3 to 3.0, more preferably from 0.5 to 2.5, and even more preferably from 0.8 to 2.0. When the temperature is within the above preferred range, the reaction proceeds stably and the reaction product precipitates easily.
[0067] The method of adding the conductive polymer aqueous dispersion to the reaction liquid is not particularly limited, and a desired amount may be added all at once in a few seconds, or may be added slowly dropwise. From the viewpoint of obtaining a conductive composite having a small particle size and increasing the conductivity, the method of adding slowly dropwise is preferred. The rate at which the conductive polymer aqueous dispersion is dropped into the reaction liquid is preferably 1 minute to 3 hours, more preferably 10 minutes to 2 hours, from the start to the end of the drop, assuming that a constant amount is continuously dropped. During the drop, it is preferable to gently stir the reaction liquid. When the temperature is within the above preferred range, the reaction proceeds stably and the reaction product precipitates easily.
[0068] The amount of the conductive polymer aqueous dispersion added dropwise to the reaction liquid is preferably 0.1 to 100 ml / min, and more preferably 1 to 10 ml / min. During the dropwise addition, it is preferable to gently stir the reaction liquid. When the temperature is within the above preferred range, the reaction proceeds stably and the reaction product precipitates easily.
[0069] When the conductive polymer dispersion is added to the reaction liquid and gently stirred, a reaction product precipitates within a few minutes to a few hours. The completion of the reaction can be confirmed by visually observing the completion of the precipitation of the reaction product.
[0070] The temperature of the reaction solution is not particularly limited and may be, for example, 5 to 40°C.
[0071] [Recovery process] This step is a step of recovering the reaction product as a precipitate. The recovery method is not particularly limited, and recovery can be performed, for example, by decantation or filtration. It is preferable that the water content of the recovered reaction product (precipitate) is as small as possible, and it is most preferable that it contains no water at all, but from a practical standpoint, it may contain water in the range of 10 mass % or less. Methods for reducing the moisture content include, for example, washing off the precipitate with an organic solvent, drying the precipitate, and the like.
[0072] [Cleaning process] It is preferable to add a washing step between the recovery step and the preparation step. The washing step is a step of washing the precipitate with an organic solvent for washing. This washing step can remove remaining water, unreacted quaternary ammonium compounds, impurities contained in the conductive polymer aqueous dispersion, and the like.
[0073] The cleaning organic solvent is preferably one that can clean the precipitate while minimizing dissolution of the precipitate. For this reason, the cleaning organic solvent is preferably an alcohol-based solvent other than isopropyl alcohol. The cleaning organic solvent may contain one type of organic solvent or two or more types of organic solvents. The washing method is not particularly limited, and for example, the precipitate may be washed by pouring an organic washing solvent over the precipitate, or the precipitate may be washed by stirring in the organic washing solvent.
[0074] [Preparation process] This step is a step of adding an organic solvent to the precipitate to obtain a conductive polymer-containing liquid.
[0075] As the organic solvent in this step, it is preferable to use the organic solvent contained in the conductive polymer-containing liquid of the first embodiment. Since the conductive complex is modified with a quaternary ammonium compound, it is preferable to use isopropyl alcohol in order to thoroughly disperse the conductive complex. In addition to isopropyl alcohol, an organic solvent may be added as desired, for example, one or more selected from alcohol-based solvents other than isopropyl alcohol. The content of each solvent contained in the organic solvent is preferably within the preferred range exemplified in the first embodiment.
[0076] It is preferable to carry out a dispersion treatment by stirring the organic solvent solution of the conductive composite obtained by adding an organic solvent to the precipitate. The stirring method is not particularly limited, and stirring with a weak shear force such as a stirrer or stirring with a dispersing machine with a high shear force (homogenizer, etc.) may be used.
[0077] The content of the conductive complex relative to the total mass of the above organic solvent solution dispersed by the high-pressure homogenizer is, for example, preferably 0.01 mass % or more and 5 mass % or less, more preferably 0.05 mass % or more and 2 mass % or less, and even more preferably 0.1 mass % or more and 1 mass % or less. When the concentration is within the above range, the dispersibility of the conductive composite can be sufficiently increased.
[0078] <Conductive laminate> A second aspect of the present invention is a conductive laminate comprising a substrate and a conductive layer formed on at least one surface of the substrate, the conductive layer being made of a cured product of the conductive polymer-containing liquid of the first aspect.
[0079] [Conductive layer] The average thickness of the conductive layer provided on at least one surface of the substrate is, for example, preferably 10 nm to 100 μm, more preferably 20 nm to 50 μm, and even more preferably 30 nm to 30 μm. When the average thickness of the conductive layer is equal to or greater than the lower limit, high conductivity can be exhibited, and when the average thickness is equal to or less than the upper limit, the adhesion of the conductive layer to the substrate is further improved.
[0080] The conductive layer of the conductive laminate of this embodiment contains a conductive complex containing a π-conjugated conductive polymer and a polyanion, and further contains a cured product of an acrylic monomer and a urethane acrylate.
[0081] [Base material] The substrate constituting the conductive laminate of this embodiment may be a substrate made of an insulating material or a substrate made of a conductive material. The shape of the substrate is not particularly limited, and examples thereof include a shape mainly having a flat surface such as a film or a substrate. Examples of insulating materials include glass, synthetic resin, and ceramics. The conductive material may be a metal, a conductive metal oxide, carbon, or the like.
[0082] (Film substrate) When a film substrate is used as the substrate, the conductive laminate becomes a conductive film. The film substrate may be, for example, a plastic film made of a synthetic resin, such as ethylene-methyl methacrylate copolymer resin, ethylene-vinyl acetate copolymer resin, polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyvinyl alcohol, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyacrylate, polycarbonate, polyvinylidene fluoride, polyarylate, styrene-based elastomer, polyester-based elastomer, polyethersulfone, polyetherimide, polyetheretherketone, polyphenylene sulfide, polyimide, cellulose triacetate, cellulose acetate propionate, etc. From the viewpoint of improving the adhesion between the film substrate and the conductive layer, the synthetic resin for the film substrate is preferably the same type of resin as the binder resin, and among these, a polyester resin such as polyethylene terephthalate is preferred.
[0083] The synthetic resin for the film substrate may be either amorphous or crystalline. The film substrate may be either unstretched or stretched. The film substrate may be subjected to a surface treatment such as a corona discharge treatment, a plasma treatment, or a flame treatment in order to further improve the adhesiveness of the conductive layer formed from the conductive polymer-containing liquid.
[0084] The average thickness of the film substrate is preferably 5 μm to 500 μm, more preferably 20 μm to 200 μm. If the average thickness of the film substrate is equal to or more than the lower limit, the film is less likely to break, and if the average thickness is equal to or less than the upper limit, the film can have sufficient flexibility. The average thickness of the film substrate is calculated by measuring the thickness at 10 randomly selected points and averaging the measured values.
[0085] (Glass substrate) Examples of the glass substrate include an alkali-free glass substrate, a soda-lime glass substrate, a borosilicate glass substrate, and a quartz glass substrate. If the substrate contains an alkali component, the conductivity of the conductive layer tends to decrease, so among the above glass substrates, an alkali-free glass is preferred. Here, the alkali-free glass refers to a glass composition in which the content of the alkali component is 0.1 mass% or less with respect to the total mass of the glass composition.
[0086] The average thickness of the glass substrate is preferably 100 μm or more and 3000 μm or less, and more preferably 100 μm or more and 1000 μm or less. If the average thickness of the glass substrate is equal to or more than the lower limit, the substrate is less likely to be broken, and if the average thickness is equal to or less than the upper limit, the substrate can contribute to making the conductive laminate thinner. The average thickness of the glass substrate is calculated by measuring the thickness at 10 randomly selected points and averaging the measured values.
[0087] The conductive layer of the conductive laminate of this embodiment has excellent resistance to atmospheric exposure. Specifically, it is desirable that the increase in the surface resistivity of the conductive layer is suppressed to preferably 10 times or less, more preferably 2 times or less, and even more preferably 1.5 times or less before and after an atmospheric exposure experiment in which the conductive laminate is left standing in a 25°C environment and exposed to the atmosphere for 10 days (240 hours). Here, the increase is represented by the ratio (R1 / R0) of the surface resistivity R1 after the atmospheric exposure experiment divided by the surface resistivity R0 before the atmospheric exposure experiment.
[0088] <Method for manufacturing conductive laminate> The conductive laminate of the second aspect of the present invention can be obtained by the following method, which comprises applying the conductive polymer-containing liquid of the first aspect to at least one surface of a substrate.
[0089] Examples of a method for applying (coating) the conductive polymer-containing liquid of the first embodiment to an arbitrary surface of a substrate include a method using a coater such as a gravure coater, a roll coater, a curtain flow coater, a spin coater, a bar coater, a reverse coater, a kiss coater, a fountain coater, a rod coater, an air doctor coater, a knife coater, a blade coater, a cast coater, or a screen coater; a method using a sprayer such as an air spray, an airless spray, or a rotor dampening; and an immersion method such as dipping.
[0090] The amount of conductive polymer-containing liquid applied to the substrate is not particularly limited, but taking into consideration uniform and even application, conductivity, and film strength, a solid content of 0.01 g / m 2 More than 10.0g / m 2 The following ranges are preferred:
[0091] The coating film made of the conductive polymer-containing liquid applied onto the substrate is dried to remove the dispersion medium, and then a process is carried out to polymerize the acrylic monomer and the urethane acrylate, thereby obtaining a conductive laminate in which a conductive layer (conductive film) is formed by hardening the coating film.
[0092] Methods for drying the coating film include heat drying, vacuum drying, etc. Examples of heat drying that can be used include hot air heating and infrared heating. When applying heat drying, the heating temperature is appropriately set depending on the dispersion medium used, but is usually within the range of 50° C. to 150° C. Here, the heating temperature is the set temperature of the drying device. A suitable drying time within the above heating temperature range is preferably 1 minute to 30 minutes, more preferably 1 minute to 10 minutes.
[0093] Radical polymerization is preferred as a method for polymerizing the acrylic monomer and urethane acrylate contained in the coating film because it is easy and reliable. When radical polymerization is applied, it is preferred to add a polymerization initiator to the conductive polymer-containing liquid in advance. Polymerization can be achieved by heating or irradiating light (active energy rays) depending on the type of polymerization initiator. Examples of active energy rays include ultraviolet rays, electron beams, and visible light. Examples of light sources that can be used for ultraviolet rays include ultra-high pressure mercury lamps, high pressure mercury lamps, low pressure mercury lamps, carbon arcs, xenon arcs, and metal halide lamps. EXAMPLES
[0094] (Production Example 1) Production of polystyrene sulfonic acid 206 g of sodium styrenesulfonate was dissolved in 1000 ml of ion-exchanged water, and while stirring at 80° C., 1.14 g of an oxidizing agent solution of ammonium persulfate previously dissolved in 10 ml of water was added dropwise over 20 minutes, and the solution was stirred for 12 hours. 1000ml of sulfuric acid diluted to 10% by mass was added to the obtained sodium styrene sulfonate-containing solution, and about 1000ml of the solvent was removed from the polystyrene sulfonic acid-containing solution by ultrafiltration. Next, 2000ml of ion-exchanged water was added to the remaining liquid, and about 2000ml of the solvent was removed by ultrafiltration, and the polystyrene sulfonic acid was washed with water. This washing operation was repeated three times. Water in the resulting solution was removed under reduced pressure to obtain colorless solid polystyrene sulfonic acid.
[0095] (Production Example 2) Synthesis of a conductive polymer dispersion containing a π-conjugated conductive polymer and a polyanion 14.2 g of 3,4-ethylenedioxythiophene and a solution in which 36.7 g of polystyrene sulfonic acid was dissolved in 2000 ml of ion-exchanged water were mixed at 20°C. The resulting mixed solution was kept at 20° C., and while stirring, 29.64 g of ammonium persulfate and 8.0 g of an oxidation catalyst solution of ferric sulfate dissolved in 200 ml of ion-exchanged water were slowly added, followed by stirring for 3 hours to allow the reaction to proceed. To the reaction solution, 2000 ml of ion-exchanged water was added, and about 2000 ml of the solvent was removed by ultrafiltration. This operation was repeated three times. Next, 200 ml of sulfuric acid diluted to 10% by mass and 2000 ml of ion-exchanged water were added to the obtained solution, and about 2000 ml of the solvent was removed by ultrafiltration. 2000 ml of ion-exchanged water was added to the remaining liquid, and about 2000 ml of the solution was removed by ultrafiltration. This operation was repeated three times. Furthermore, 2000 ml of ion-exchanged water was added to the obtained solution, and about 2000 ml of the solvent was removed by ultrafiltration. This operation was repeated five times to obtain a polystyrene sulfonate-doped poly(3,4-ethylenedioxythiophene) (PEDOT-PSS) aqueous dispersion with a concentration of 1.2 mass%. The PSS content in the PEDOT-PSS was 75 mass%.
[0096] (Production Example 3) Reaction with quaternary ammonium salt 100g of the PEDOT-PSS aqueous dispersion prepared in Production Example 2 was added dropwise to the organic layer (organic solution) prepared by dissolving 2.4g of tetraoctylammonium bromide in 200g of ethanol, and the mixture was stirred for 30 minutes. As a result, a reaction product of tetraoctylammonium bromide and a conductive complex was precipitated. This precipitate was collected by filtration, 100g of isopropyl alcohol was added, and the precipitate was lightly suspended while stirring for 30 minutes, after which the precipitate was collected by filtration again and washed. As a result, 1.1g of a conductive complex having the aforementioned substituent (C) was obtained. Next, 1.1 g of the conductive complex obtained above was mixed with 274 g of isopropyl alcohol, and the mixture was dispersed with a high-pressure homogenizer to obtain an isopropyl alcohol solution of the conductive complex.
[0097] (Production Example 4) Reaction with amine compounds 100g of the PEDOT-PSS aqueous dispersion prepared in Production Example 2 was added dropwise to an organic layer prepared by dissolving 5g of trioctylamine in 200g of ethanol, and the mixture was stirred for 30 minutes. As a result, a reaction product of trioctylamine and a conductive complex was precipitated. This precipitate was filtered and washed in the same manner as in Production Example 3, yielding 1.1g of a conductive complex that had reacted with trioctylamine. Next, 1.1 g of the conductive complex obtained above was mixed with 274 g of isopropyl alcohol, and the mixture was dispersed with a high-pressure homogenizer to obtain an isopropyl alcohol solution of the conductive complex.
[0098] Example 1 16 g of pentaerythritol triacrylate (Kyoeisha Chemical Co., Ltd., product name: Light Acrylate PE-3A), 2.8 g of urethane acrylate (Negami Chemical Industries, Ltd., product name: Art Resin 904M, non-volatile content concentration 80 mass%, 10 functional groups), and 5 g of propylene glycol monomethyl ether were added to 50 g of isopropyl alcohol and stirred for 30 minutes. Then, 1.6 g of 1-hydroxycyclohexyl phenyl ketone (IGM Resins, product name: Omnirad 184), a photopolymerization initiator, was added and stirred for 30 minutes, and 25 g of the isopropyl alcohol solution of the conductive complex obtained in Production Example 3 was added and stirred for 30 minutes to obtain the target conductive polymer-containing liquid. The obtained conductive polymer-containing liquid was applied to a polyester film (Toray Industries, Inc., Cosmoshine A4300) using a bar coater No. 8, and the coating film (conductive layer) was dried at 100°C for 1 minute. Next, the coating film was cured by irradiating it with ultraviolet light using an ultraviolet irradiator, to obtain a conductive hard coat film (conductive film). The surface resistivity R0 of this conductive film was measured, and the results are shown in Table 1. Next, this conductive film was left to stand in an environment at 25°C and exposed to the atmosphere for 10 days. The results of measuring the surface resistivity R1 of the conductive film after this exposure to the atmosphere and the amount of change expressed as the ratio R1 / R0 are shown in Table 1. The closer the value of this amount of change (common logarithm: x) is to 0, the less change there is, which means that the resistance to atmospheric exposure is excellent.
[0099] Example 2 A conductive hard coat film was obtained in the same manner as in Example 1, except that the 2.8 g of urethane acrylate in Example 1 was changed to 2.3 g of Acrylit 8UX-122A (manufactured by Taisei Fine Chemical Co., Ltd., non-volatile content concentration 99.9 mass%), and the surface resistivities R0 and R1 were measured.
[0100] Example 3 A conductive hard coat film was obtained in the same manner as in Example 1, except that 15 g of 2-hydroxyethylacrylamide was further added to the conductive polymer-containing liquid, and the surface resistivities R0 and R1 were measured.
[0101] Example 4 A conductive hard coat film was obtained in the same manner as in Example 3, except that 15 g of 2-hydroxyethylacrylamide was changed to 15 g of N,N-dimethylacrylamide, and the surface resistivities R0 and R1 were measured.
[0102] Example 5 A conductive hard coat film was obtained in the same manner as in Example 3, except that 15 g of 2-hydroxyethylacrylamide was changed to 15 g of N,N-diethylacrylamide, and the surface resistivities R0 and R1 were measured.
[0103] Example 6 A conductive hard coat film was obtained in the same manner as in Example 3, except that 15 g of 2-hydroxyethylacrylamide was changed to 15 g of N-acroylmorpholine, and the surface resistivities R0 and R1 were measured.
[0104] Example 7 A conductive hard coat film was obtained in the same manner as in Example 1, except that 3 g of an organosilica compound (Nissan Chemical Industries, Ltd., MEK-AC-2140Y, non-volatile content concentration: 40 mass%, dispersed in methyl ethyl ketone) was further added to the conductive polymer-containing liquid, and the surface resistivities R0 and R1 were measured.
[0105] Example 8 16g of pentaerythritol triacrylate (Kyoeisha Chemical Co., Ltd., product name: Light Acrylate PE-3A), 8.6g of STA-SiA TAZ-136 (Taisei Fine Chemical Co., Ltd., non-volatile content concentration 40% by mass, urethane acrylate: 15% by mass, organosilica compound: 25% by mass), and 5g of propylene glycol monomethyl ether were added to 43.8g of isopropanol and stirred for 30 minutes. Then, 1.6g of 1-hydroxycyclohexyl phenyl ketone (IGM Resins, product name: Omnirad 184), which is a photopolymerization initiator, was added and stirred for 30 minutes, and then 25g of the isopropyl alcohol solution of the conductive complex obtained in Production Example 3 was added and stirred for 30 minutes to obtain the target conductive polymer-containing liquid. The obtained conductive polymer-containing liquid was applied to a polyester film (Toray Industries, Inc., Cosmoshine A4300) using a bar coater No. 8, and the coating film (conductive layer) was dried at 100°C for 1 minute. Next, the coating film was irradiated with ultraviolet light using an ultraviolet irradiator to harden the coating film, thereby obtaining a conductive hard coat film (conductive film). The surface resistivities R0 and R1 of this conductive film were measured in the same manner as in Example 1.
[0106] Example 9 A conductive hard coat film was obtained in the same manner as in Example 8, except that 15 g of N,N-dimethylacrylamide was further added to the conductive polymer-containing liquid, and the surface resistivities R0 and R1 were measured.
[0107] Comparative Example 1 A conductive hard coat film was obtained in the same manner as in Example 1, except that Art Resin 904M was not added to the conductive polymer-containing liquid, and the surface resistivities R0 and R1 were measured.
[0108] Comparative Example 2 A conductive hard coat film was obtained in the same manner as in Example 1, except that the isopropyl alcohol solution of the conductive complex obtained in Production Example 4 was used, and the surface resistivities R0 and R1 were measured.
[0109] [Surface resistivity measurement] For the conductive films produced in each example, the surface resistivity of the conductive layer was measured using a resistivity meter (Hiresta manufactured by Nitto Seiko Analytech Co., Ltd.) under the condition of an applied voltage of 10V.
[0110] [Table 1]
[0111] The conductive polymer-containing liquid of each example according to the present invention contains a conductive complex, an acrylic monomer, and a urethane acrylate, and the excess anion groups of the conductive complex that are not involved in the doping of the polyanion are modified by reacting with a quaternary ammonium compound. The surface resistivity of the conductive layer formed using this conductive polymer-containing liquid was maintained sufficiently low even after exposure to the atmosphere, and the conductive layer had excellent resistance to exposure to the atmosphere. From a comparison between Examples 1 and 2 and Examples 3 to 6, it can be seen that the atmospheric exposure resistance is improved when two or more kinds of acrylic monomers are contained, rather than when only one kind is contained. Moreover, a comparison between Examples 1 to 6 and Examples 7 to 9 reveals that when the conductive polymer-containing liquid contains an organosilica compound, the resistance to exposure to the atmosphere is remarkably excellent.
[0112] In Comparative Example 1, the conductive polymer-containing liquid did not contain urethane acrylate, and therefore the resistance to exposure to the atmosphere was poor. In Comparative Example 2, the conductive complex was reacted with a tertiary amine, and therefore the resistance to exposure to the atmosphere was poor.
Claims
1. A conductive polymer-containing liquid containing a conductive complex including a π-conjugated conductive polymer and a polyanion, an organic solvent, one or more acrylic monomers, and a urethane acrylate other than the acrylic monomers, the polyanion is modified by reacting a portion of an anionic group of the polyanion with a quaternary ammonium compound; the acrylic monomer comprises pentaerythritol triacrylate; the π-conjugated conductive polymer contains poly(3,4-ethylenedioxythiophene); The conductive polymer-containing liquid, wherein the polyanion includes polystyrene sulfonic acid.
2. The conductive polymer-containing liquid according to claim 1 , further comprising a photopolymerization initiator.
3. The conductive polymer-containing liquid according to claim 1 or 2, further comprising a silica compound.
4. The conductive polymer-containing liquid according to any one of claims 1 to 3, wherein the organic solvent contains at least one selected from the group consisting of isopropyl alcohol, methyl ethyl ketone, and propylene glycol monomethyl ether.
5. The conductive polymer-containing liquid according to any one of claims 1 to 4, wherein the acrylic monomer further comprises 2-hydroxyethylacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, or N-acroylmorpholine.
6. The conductive polymer-containing liquid according to any one of claims 1 to 5, wherein the quaternary ammonium compound has at least one hydrocarbon group having 4 to 32 carbon atoms.
7. The conductive polymer-containing liquid according to claim 1 , wherein the quaternary ammonium compound comprises tetraoctylammonium.
8. A conductive laminate comprising a substrate and a conductive layer formed on at least a portion of the substrate, the conductive layer being made of a cured product of the conductive polymer-containing liquid according to any one of claims 1 to 7.
9. 9. The conductive laminate according to claim 8, wherein an increase in the surface resistivity of the conductive layer of the conductive laminate is suppressed to 10 times or less before and after an atmospheric exposure experiment in which the conductive laminate is left stationary in a 25°C environment and exposed to the atmosphere for 10 days.
Citation Information
Patent Citations
Composition for an antistatic release agent and antistatic release film
JP2014189597A
Conductive polymer dispersion liquid and conductive coating film
JP2015131890A
Conductive coating liquid and conductive coating film
JP2017088695A
Conductive polymer dispersion liquid and method for producing the same, and method for producing conductive film
JP2018115269A
Conductive polymer composition, conductive polymer film, and electrolytic capacitor
JP2019192752A